Фізико-хімічні умови формування баденських солей Українського Передкарпаття (ділянка Гринівка) - Галамай, А. (Геологія і геохімія горючих копалин, 2010)
Досліджено характер розподілу включень різного генетичного типу в кристалах галіту в розрізі баденських соленосних відкладів на ділянці Гринівка. Вивчено їхню форму, хімічний та фазовий склад. За результатами досліджень первинних включень у седиментаційному галіті встановлено, що розсоли солеродного басейну є морськими і відповідають сульфатному хімічному типу. За хімічним складом вони близькі до сучасної океанічної води, згущеної до осадження галіту, і відрізняються від неї трохи пониженим вмістом іона SO4 . Солі перекристалізовувалися за низької температури та близького до атмосферного тиску. У перекристалізації брали участь різною мірою метаморфізовані захоронені седиментаційні розсоли. З’ясовано, що включення з нафтовою фазою утворилися в галіті на пізній стадії діагенезу соляних відкладів. Вміст метану в розсолах цих включень підвищений. Ореоли розсіювання у вигляді включень з нафтовою фазою, на нашу думку, можна використовувати як індикатор нафтогазоносності підстилаючих евапорити осадових товщ. The chemical composition of brines in primary inclusions in halite from Badenian evaporite formations in the Ukrainian part of the Carpathian Foredeep have been studied. Investigated area is located near Kalush. Data on the chemical composition of brines in inclusions in sedimentary and postsedimentary halite are very important sources of information for revealing evaporite genesis and conditions of its forming. The results show that the basin brine belonged to the Na-K-Mg-Cl-SO₄ -type. The seawater was the main source of salt formation, and the ratio of the ions concentration was close to those in the modern seawater saturated with NaCl by slightly decreased content of SO₄²⁻. The brine salinity did not rise over the initial stage of halite precipitation. Significant fluctuations in concentration of brines in the vertical profile of salt deposit are not observed. The reason of decreased content of SO₄ -ions was the chemical evolution of seawater in the Cenozoic, in part, probably, the inflow of continental water. The investigated secondary inclusions were located, as a rule, in the same chevron structures, but they differed from primary inclusions in terms of irregular shape and large dimensions. Brine inclusions in early diagenetic halite as well as in sedimentary ones have Na-K-Mg-Cl-SO₄ -composition. When compared to sedimentary halite, the brine inclusions in diagenetic halite are characterized by decreased concentration of major ions. The most interesting are presented inclusions with hydrocarbons. They are mainly irregular in shape and rarely cubic. Hydrocarbons form microdroples or thin red-brown crusts. Such inclusions were formed at the latest diagenetic stage of the salt deposits. The brine with oil migration through salt occurred under low temperature. Areas of dispersion are present as fluid inclusions with oil. In our opinion, this area may be used as indicator of oil and gas bearing of underlying evaporite sedimentary beds.